Intrinsic and interfacial kinetics of perovskite solar cells under photo and bias-induced degradation and recovery. Issue 31 (21st July 2017) - Yadav, Pankaj; Prochowicz, Daniel; Alharbi, Essa A.; Zakeeruddin, Shaik M.; Grätzel, Michael
Abstract : Perovskite solar cells (PSCs) have emerged as a potential candidate for high efficiency low-cost photovoltaic technology. Abstract : Perovskite solar cells (PSCs) have emerged as a potential candidate for high efficiency low-cost photovoltaic technology. However, the intrinsic and interfacial responses of PSCs under photo and bias-induced degradation and recovery have not been clearly understood. Herein, the influence of illumination and bias on the intrinsic and interfacial characteristics of PSCs is examined by studying the role of trap states, perovskite dielectric relaxation phenomena, transport and recombination characteristics as well as ion movements. We found that under illumination and bias stress conditions, the photo-current at short circuit conditions was decreased in a reversible way and recovered to its initial value after keeping the device in the dark. On the basis of electrical measurements and analysis, we conclude that the full recovery of PSC performance was limited by an increase in the relative dielectric constant, series and shunt resistances and enhanced recombination pathways under stimuli conditions.